New energy automobile battery gel with fire extinguishing function
By using nano -aluminum hydroxide, nano -magnesium hydroxide, and nano -nanoscular silicon oxide in the new energy vehicle battery glue, the existing battery sealing glue has the problem of insufficient performance in flame retardant and fire extinguishing. Efficient flame retardant and fire extinguishing effect.
Patent Information
- Application Number
- CN202411325157.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing new energy vehicle battery sealants have insufficient performance in flame retardant and fire extinguishing, and cannot effectively suppress the spread of battery fires. Traditional flame retardants may affect other performances of sealants.
Using nanomaterials such as nanoaluminum hydroxide, nanomagnesium hydroxide and nanosilica, combined with silicone rubber, polyurethane and epoxy resin, a new energy vehicle battery glue with fire extinguishing function is prepared.
It significantly improves the flame retardant performance and fire-extinguishing ability of the battery glue, can achieve good flame retardant effect at a lower addition amount, enhances the strength and hardness of the battery glue, and at the same time reduces the losses caused by fire.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery glue, and in particular to a new energy vehicle battery glue with a fire extinguishing function. Background Art
[0002] With the rapid development of new energy vehicles, the safety of power batteries has received increasing attention. During operation, new energy vehicle batteries may overheat, short-circuit, etc. due to various reasons, thus causing fire accidents. In order to improve the safety of new energy vehicles, higher requirements are placed on battery sealants.
[0003] At present, the battery sealants for new energy vehicles on the market are mainly used to achieve sealing functions, and their performance in flame retardancy and fire extinguishing is relatively weak. Existing sealants usually use traditional organic materials. Although they can play a role in sealing, waterproofing, and dustproofing to a certain extent, they cannot effectively suppress the spread of fire in the face of emergencies such as battery fires, and may even aggravate the harm of fire due to their own combustion.
[0004] The existing battery sealants have the following obvious deficiencies:
[0005] 1. Limited flame retardancy. Most existing new energy vehicle battery sealants are prone to burn when exposed to open flames, and their flame retardancy is not sufficient to cope with emergency situations in which the battery catches fire. Even if some sealants have a certain flame retardant effect, a large amount of flame retardants often need to be added, which not only increases costs but may also have a negative impact on other properties of the sealant. Traditional flame retardants may affect the adhesive properties and aging resistance of the sealant, resulting in sealing failure, cracking and other problems during long-term use of the sealant.
[0006] 2. Lack of fire extinguishing function. The current sealant has almost no fire extinguishing function and cannot quickly extinguish the flames in the early stage of battery fire. It can only rely on external fire extinguishing equipment to extinguish the fire. This delays the best time to extinguish the fire to a certain extent and increases the losses caused by the fire.
[0007] The existing new energy vehicle battery sealant has obvious deficiencies in flame retardancy and fire extinguishing, and cannot meet the high requirements of the new energy vehicle industry for battery safety. Therefore, it is of great practical significance to develop a new energy vehicle battery sealant with good flame retardancy and fire extinguishing effect. Summary of the invention
[0008] In view of the defects of the prior art, the purpose of the present invention is to provide a new energy vehicle battery gel with fire extinguishing function and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0009] The present invention solves the technical problem by adopting the following technical solution:
[0010] The present invention provides a new energy vehicle battery glue with a fire extinguishing function, comprising the following raw materials in parts by weight:
[0011] 24-30 parts of organic silicone rubber, 17-23 parts of polyurethane, 8-12 parts of epoxy resin, 4-8 parts of nano aluminum hydroxide, 6-10 parts of nano magnesium hydroxide, 4-6 parts of zinc borate, 4-6 parts of phosphonate, and 4-8 parts of nano silicon dioxide.
[0012] Furthermore, the new energy vehicle battery glue with fire extinguishing function comprises the following raw materials in parts by weight:
[0013] 27 parts of organic silicon rubber, 20 parts of polyurethane, 10 parts of epoxy resin, 6 parts of nano aluminum hydroxide, 8 parts of nano magnesium hydroxide, 5 parts of zinc borate, 5 parts of phosphonate, and 6 parts of nano silicon dioxide.
[0014] Furthermore, the preparation method of the nano aluminum hydroxide is:
[0015] An aluminum sulfate aqueous solution is prepared with a polymer protective agent added thereto, wherein the polymer protective agent is polyethylene glycol, the amount of polyethylene glycol added is 4%-5% of the mass of the aluminum sulfate, and the concentration of the aluminum sulfate solution is 1-2 mol / L;
[0016] The aluminum sulfate aqueous solution was placed in a homogenizing emulsification reactor, heated to 45° C., and stirred at 1600 rpm for 30 minutes;
[0017] Slowly drip a sodium hydroxide solution with a concentration of 0.5-1.0 mol / L into the reactor, and stir continuously, control the rotation speed to 3000-7000 rpm, and control the reaction temperature to 25-45°C to obtain an aluminum hydroxide suspension;
[0018] The obtained aluminum hydroxide suspension was cooled, aged, and filtered, and the obtained filter cake was washed with deionized water; in this process, the aging treatment temperature was 20° C. and the time was 12 hours;
[0019] The azeotropic solution n-butanol solution is added to the filter cake obtained above, and the mixture is stirred and slurried, and then azeotropic distillation is performed until the water is completely removed, and then the distillation is continued to evaporate the azeotropic solvent n-butanol, and then the obtained colloid is dried to finally obtain nano aluminum hydroxide particles; wherein, 0.5-0.7 ml of the azeotropic solvent n-butanol is added to each gram of sodium hydroxide colloid filter cake, and the drying temperature of the obtained colloid is 100-130°C, and the drying time is 6-12 hours.
[0020] Furthermore, the preparation method of the nano magnesium hydroxide is:
[0021] Homogenization: fully homogenize the desulfurization wastewater to completely precipitate the insoluble matter to obtain the primary supernatant, take samples to test the water quality of the primary supernatant, and detect the concentration of each ion;
[0022] Pretreatment: The primary supernatant is pretreated to remove reducing ions, oil, COD and heavy metal ions to obtain a suspension, which is then separated and precipitated to obtain a secondary supernatant;
[0023] Separating calcium ions: adding an excess amount of sodium carbonate solution to the secondary supernatant, wherein the amount of sodium carbonate solution added is in accordance with a molar ratio of carbonate ions to calcium ions of 1.1-1.3; adjusting the pH value to 7.0-8.5 with a sodium hydroxide solution having a concentration of 15 wt % to generate a calcium carbonate precipitate, the reaction time is 30 min, the reaction temperature is 30-35° C., separating the calcium carbonate precipitate from the supernatant, and obtaining a tertiary supernatant;
[0024] Preparation of magnesium hydroxide product: adding dispersant and excess ammonia water to the tertiary supernatant, obtaining magnesium hydroxide precipitate after complete reaction, separating the magnesium hydroxide precipitate and the quaternary supernatant after sufficient aging; filtering the magnesium hydroxide precipitate, drying and dehydrating to obtain the magnesium hydroxide product, grinding the magnesium hydroxide product with a nano grinder to obtain nano-scale magnesium hydroxide powder; wherein the concentration of ammonia water is 25%, and the amount of ammonia water added is in accordance with the ratio of ammonia water to magnesium ion molar ratio of 2.2; urea is solid, and the amount of urea added is in accordance with the ratio of urea molar ratio to magnesium ion molar ratio of 1.1; the reaction temperature is 110°C, the reaction time is 5h, the pressure in the reactor is 2atm, and the pH is controlled to be 10; aging is performed for 1.5h after the reaction, and the aging temperature is 70-80°C.
[0025] Furthermore, the dispersant is PEG-800, and the dosage is 2 ml / 100 ml, that is, 2 ml of the dispersant is added to every 100 ml of the tertiary supernatant.
[0026] Furthermore, the amount of sodium carbonate solution added is such that the molar ratio of carbonate ions to calcium ions is 1.2.
[0027] Further, the preparation method of the nano silicon dioxide is:
[0028] Slowly drop a certain amount of ethyl orthosilicate into a reactor containing deionized water, wherein the volume ratio of ethyl orthosilicate to deionized water is controlled between 1:5 and 1:10; at the same time, turn on the stirring device, and set the stirring speed at 300-500 rpm to ensure that ethyl orthosilicate and water are fully mixed; the temperature in the reactor is maintained at 20-30°C; continue stirring and keep the temperature stable for 1-2 hours to ensure that the hydrolysis reaction is fully carried out;
[0029] Slowly drip ammonia water into the solution after the hydrolysis reaction, and the dripping speed of ammonia water should be controlled at 5-10 drops per minute to avoid uneven reaction due to excessive local ammonia concentration; the amount of ammonia water added is determined according to the amount of tetraethyl orthosilicate, and the molar ratio of ammonia water to tetraethyl orthosilicate is between 3:1 and 5:1; the stirring speed is maintained at 300-500 rpm, and the reaction temperature is still controlled at 20-30°C; stirring should be continued for 2-3 hours during the reaction to allow the nano-silicon dioxide particles to fully grow and stabilize;
[0030] After the reaction is completed, the obtained nano-silicon dioxide suspension is centrifuged and washed 4 times; an appropriate amount of deionized water is added each time, and the mixture is stirred evenly and then centrifuged. The centrifugal speed is set at 3000-5000 rpm and the centrifugal time is 10-15 minutes;
[0031] The washed nano-silicon dioxide suspension is filtered through a microporous filter membrane, and the pore size of the filter membrane is selected to be 0.2-0.45 microns;
[0032] The filtered nano-silicon dioxide solid is placed in a drying oven for drying, the drying temperature is set at 80-120°C, and the drying time is 6-12 hours;
[0033] The dried nano-silicon dioxide solid is ground for 2-4 hours to disperse the agglomerated nano-silicon dioxide particles into individual nano-particles;
[0034] The ground nano-silicon dioxide powder is sieved through a sieving device to obtain a nano-silicon dioxide product with uniform particle size.
[0035] Furthermore, the volume ratio of ethyl orthosilicate to deionized water is 1:8.
[0036] Furthermore, the molar ratio of ammonia water to tetraethyl orthosilicate is 3:1.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] The new energy vehicle battery glue with fire extinguishing function provided by the present application can improve the flame retardant performance of the battery glue due to the unique physical and chemical properties of nanomaterials. Nano silicon dioxide can enhance the strength and hardness of the battery glue, and at the same time improve its flame retardant performance. The flame retardant effect of nano magnesium hydroxide and nano aluminum hydroxide is also very good, and a good flame retardant effect can be achieved at a lower addition amount. DETAILED DESCRIPTION
[0039] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] A new energy vehicle battery glue with fire extinguishing function, comprising the following raw materials in parts by weight:
[0041] 24-30 parts of organic silicone rubber, 17-23 parts of polyurethane, 8-12 parts of epoxy resin, 4-8 parts of nano aluminum hydroxide, 6-10 parts of nano magnesium hydroxide, 4-6 parts of zinc borate, 4-6 parts of phosphonate, and 4-8 parts of nano silicon dioxide.
[0042] Furthermore, the new energy vehicle battery glue with fire extinguishing function comprises the following raw materials in parts by weight:
[0043] 27 parts of organic silicon rubber, 20 parts of polyurethane, 10 parts of epoxy resin, 6 parts of nano aluminum hydroxide, 8 parts of nano magnesium hydroxide, 5 parts of zinc borate, 5 parts of phosphonate, and 6 parts of nano silicon dioxide.
[0044] Furthermore, the preparation method of the nano aluminum hydroxide is:
[0045] An aluminum sulfate aqueous solution is prepared with a polymer protective agent added thereto, wherein the polymer protective agent is polyethylene glycol, the amount of polyethylene glycol added is 4%-5% of the mass of the aluminum sulfate, and the concentration of the aluminum sulfate solution is 1-2 mol / L;
[0046] The aluminum sulfate aqueous solution was placed in a homogenizing emulsification reactor, heated to 45° C., and stirred at 1600 rpm for 30 minutes;
[0047] Slowly drip a sodium hydroxide solution with a concentration of 0.5-1.0 mol / L into the reactor, and stir continuously, control the rotation speed to 3000-7000 rpm, and control the reaction temperature to 25-45°C to obtain an aluminum hydroxide suspension;
[0048] The obtained aluminum hydroxide suspension was cooled, aged, and filtered, and the obtained filter cake was washed with deionized water; in this process, the aging treatment temperature was 20° C. and the time was 12 hours;
[0049] The azeotropic solution n-butanol solution is added to the filter cake obtained above, and the mixture is stirred and slurried, and then azeotropic distillation is performed until the water is completely removed, and then the distillation is continued to evaporate the azeotropic solvent n-butanol, and then the obtained colloid is dried to finally obtain nano aluminum hydroxide particles; wherein, 0.5-0.7 ml of the azeotropic solvent n-butanol is added to each gram of sodium hydroxide colloid filter cake, and the drying temperature of the obtained colloid is 100-130°C, and the drying time is 6-12 hours.
[0050] Furthermore, the preparation method of the nano magnesium hydroxide is:
[0051] Homogenization: fully homogenize the desulfurization wastewater to completely precipitate the insoluble matter to obtain the primary supernatant, take samples to test the water quality of the primary supernatant, and detect the concentration of each ion;
[0052] Pretreatment: The primary supernatant is pretreated to remove reducing ions, oil, COD and heavy metal ions to obtain a suspension, which is then separated and precipitated to obtain a secondary supernatant;
[0053] Separating calcium ions: adding an excess amount of sodium carbonate solution to the secondary supernatant, wherein the amount of sodium carbonate solution added is in accordance with a molar ratio of carbonate ions to calcium ions of 1.1-1.3; adjusting the pH value to 7.0-8.5 with a sodium hydroxide solution having a concentration of 15 wt % to generate a calcium carbonate precipitate, the reaction time is 30 min, the reaction temperature is 30-35° C., separating the calcium carbonate precipitate from the supernatant, and obtaining a tertiary supernatant;
[0054] Preparation of magnesium hydroxide product: adding dispersant and excess ammonia water to the tertiary supernatant, obtaining magnesium hydroxide precipitate after complete reaction, separating the magnesium hydroxide precipitate and the quaternary supernatant after sufficient aging; filtering the magnesium hydroxide precipitate, drying and dehydrating to obtain the magnesium hydroxide product, grinding the magnesium hydroxide product with a nano grinder to obtain nano-scale magnesium hydroxide powder; wherein the concentration of ammonia water is 25%, and the amount of ammonia water added is in accordance with the ratio of ammonia water to magnesium ion molar ratio of 2.2; urea is solid, and the amount of urea added is in accordance with the ratio of urea molar ratio to magnesium ion molar ratio of 1.1; the reaction temperature is 110°C, the reaction time is 5h, the pressure in the reactor is 2atm, and the pH is controlled to be 10; aging is performed for 1.5h after the reaction, and the aging temperature is 70-80°C.
[0055] Furthermore, the dispersant is PEG-800, and the dosage is 2 ml / 100 ml, that is, 2 ml of the dispersant is added to every 100 ml of the tertiary supernatant.
[0056] Furthermore, the amount of sodium carbonate solution added is such that the molar ratio of carbonate ions to calcium ions is 1.2.
[0057] Further, the preparation method of the nano silicon dioxide is:
[0058] Slowly drop a certain amount of ethyl orthosilicate into a reactor containing deionized water, wherein the volume ratio of ethyl orthosilicate to deionized water is controlled between 1:5 and 1:10; at the same time, turn on the stirring device, and set the stirring speed at 300-500 rpm to ensure that ethyl orthosilicate and water are fully mixed; the temperature in the reactor is maintained at 20-30°C; continue stirring and keep the temperature stable for 1-2 hours to ensure that the hydrolysis reaction is fully carried out;
[0059] Slowly drip ammonia water into the solution after the hydrolysis reaction, and the dripping speed of ammonia water should be controlled at 5-10 drops per minute to avoid uneven reaction due to excessive local ammonia concentration; the amount of ammonia water added is determined according to the amount of tetraethyl orthosilicate, and the molar ratio of ammonia water to tetraethyl orthosilicate is between 3:1 and 5:1; the stirring speed is maintained at 300-500 rpm, and the reaction temperature is still controlled at 20-30°C; stirring should be continued for 2-3 hours during the reaction to allow the nano-silicon dioxide particles to fully grow and stabilize;
[0060] After the reaction is completed, the obtained nano-silicon dioxide suspension is centrifuged and washed 4 times; an appropriate amount of deionized water is added each time, and the mixture is stirred evenly and then centrifuged. The centrifugal speed is set at 3000-5000 rpm and the centrifugal time is 10-15 minutes;
[0061] The washed nano-silicon dioxide suspension is filtered through a microporous filter membrane, and the pore size of the filter membrane is selected to be 0.2-0.45 microns;
[0062] The filtered nano-silicon dioxide solid is placed in a drying oven for drying, the drying temperature is set at 80-120°C, and the drying time is 6-12 hours;
[0063] The dried nano-silicon dioxide solid is ground for 2-4 hours to disperse the agglomerated nano-silicon dioxide particles into individual nano-particles;
[0064] The ground nano-silicon dioxide powder is sieved through a sieving device to obtain a nano-silicon dioxide product with uniform particle size.
[0065] Furthermore, the volume ratio of ethyl orthosilicate to deionized water is 1:8.
[0066] Furthermore, the molar ratio of ammonia water to tetraethyl orthosilicate is 3:1.
[0067] Example 1.
[0068] A new energy vehicle battery glue with fire extinguishing function, comprising the following raw materials in parts by weight:
[0069] 27 parts of organic silicon rubber, 20 parts of polyurethane, 10 parts of epoxy resin, 6 parts of nano aluminum hydroxide, 8 parts of nano magnesium hydroxide, 5 parts of zinc borate, 5 parts of phosphonate, and 6 parts of nano silicon dioxide.
[0070] The specific preparation process of new energy vehicle battery glue with fire extinguishing function is:
[0071] Add silicone rubber, polyurethane and epoxy resin into the reactor, turn on the stirring device, set the stirring speed to 150 rpm, and ensure that they are fully mixed;
[0072] Add zinc borate and phosphonate in batches, and increase the stirring speed to 400 rpm to ensure that zinc borate and phosphonate are evenly dispersed in the material.
[0073] Use a high-speed disperser to slowly add nano aluminum hydroxide, nano magnesium hydroxide, and nano silicon dioxide into the system. The speed of the high-speed disperser is set to 4000 rpm and the dispersion time is 1.5 hours to ensure that the nano materials are evenly dispersed and play a synergistic role.
[0074] Transfer the mixed sealant to the vacuum degassing equipment, turn on the vacuum pump, and perform vacuum degassing treatment; the vacuum degree is set to -0.1MPa, and the degassing time is 60 minutes to remove bubbles in the sealant and improve product quality.
[0075] The preparation method of nano aluminum hydroxide of the present embodiment is:
[0076] An aqueous solution of aluminum sulfate added with a polymer protective agent is prepared, wherein the polymer protective agent is polyethylene glycol, the amount of polyethylene glycol added is 4.5% of the mass of aluminum sulfate, and the concentration of the aluminum sulfate solution is 1.5 mol / L;
[0077] The aluminum sulfate aqueous solution was placed in a homogenizing emulsification reactor, heated to 45° C., and stirred at 1600 rpm for 30 minutes;
[0078] Slowly drip a sodium hydroxide solution with a concentration of 0.8 mol / L into the reactor, and stir continuously, control the speed to 5000 rpm, and control the reaction temperature to 35°C to obtain an aluminum hydroxide suspension;
[0079] The obtained aluminum hydroxide suspension was cooled, aged, and filtered, and the obtained filter cake was washed with deionized water; in this process, the aging treatment temperature was 20° C. and the time was 12 hours;
[0080] The azeotropic solution of n-butanol solution is added to the filter cake obtained above, and the mixture is stirred and slurried, and then azeotropic distillation is performed until the water is completely removed, and then the distillation is continued to evaporate the azeotropic solvent n-butanol, and then the obtained colloid is dried to finally obtain nano aluminum hydroxide particles; wherein, 0.6 ml of the azeotropic solvent n-butanol is added to each gram of sodium hydroxide colloid filter cake, and the drying temperature of the obtained colloid is 115° C., and the drying time is 9 hours.
[0081] The preparation method of nano magnesium hydroxide of the present embodiment is:
[0082] Homogenization: fully homogenize the desulfurization wastewater to completely precipitate the insoluble matter to obtain the primary supernatant, take samples to test the water quality of the primary supernatant, and detect the concentration of each ion;
[0083] Pretreatment: The primary supernatant is pretreated to remove reducing ions, oil, COD and heavy metal ions to obtain a suspension, which is then separated and precipitated to obtain a secondary supernatant;
[0084] Separating calcium ions: adding an excess amount of sodium carbonate solution to the secondary supernatant, the amount of sodium carbonate solution added being based on a molar ratio of carbonate ions to calcium ions of 1.2; adjusting the pH value to 7.8 with a 15wt% sodium hydroxide solution to generate a calcium carbonate precipitate, the reaction time being 30 minutes, the reaction temperature being 33°C, and separating the calcium carbonate precipitate from the supernatant to obtain a tertiary supernatant;
[0085] Preparation of magnesium hydroxide product: adding PEG-800 and excess ammonia water to the third-level supernatant, the PEG-800 addition amount is 2ml / 100ml, and magnesium hydroxide precipitate is obtained after the reaction is complete, and the magnesium hydroxide precipitate and the fourth-level supernatant are separated after sufficient aging; filtering the magnesium hydroxide precipitate, drying and dehydrating to obtain the magnesium hydroxide product, and grinding the magnesium hydroxide product with a nano grinder to obtain nano-scale magnesium hydroxide powder; wherein the ammonia water concentration is 25%, and the ammonia water addition amount is in accordance with the ratio of ammonia water to magnesium ion molar ratio of 2.2; urea is solid, and the addition amount is in accordance with the ratio of urea molar ratio to magnesium ion molar ratio of 1.1; the reaction temperature is 110°C, the reaction time is 5h, the pressure in the reactor is 2atm, and the pH is controlled to be 10; aging is performed for 1.5h after the reaction, and the aging temperature is 75°C.
[0086] The preparation method of the nano silicon dioxide of the present embodiment is:
[0087] A certain amount of tetraethyl orthosilicate was slowly added dropwise to a reactor containing deionized water, and the volume ratio of tetraethyl orthosilicate to deionized water was controlled between 1:8; at the same time, a stirring device was turned on, and the stirring speed was set at 400 rpm to ensure that the tetraethyl orthosilicate and water were fully mixed; the temperature in the reactor was maintained at 25°C; stirring was continued and the temperature was kept stable for 1.5 hours to ensure that the hydrolysis reaction was fully carried out;
[0088] Slowly add ammonia water to the solution after the hydrolysis reaction, and the speed of ammonia water addition should be controlled at 8 drops per minute to avoid uneven reaction due to excessive local ammonia water concentration; the amount of ammonia water added is determined according to the amount of tetraethyl orthosilicate, and the molar ratio of ammonia water to tetraethyl orthosilicate is 4:1; the stirring speed is maintained at 400 rpm, and the reaction temperature is still controlled at 25°C; stirring should be continued for 2.5 hours during the reaction to allow the nano-silicon dioxide particles to fully grow and stabilize;
[0089] After the reaction is completed, the obtained nano-silicon dioxide suspension is centrifuged and washed 4 times; each time, an appropriate amount of deionized water is added, and the mixture is stirred evenly and then centrifuged. The centrifugal speed is set at 4000 rpm and the centrifugal time is 12 minutes;
[0090] The washed nano-silicon dioxide suspension is filtered through a microporous filter membrane, and the pore size of the filter membrane is selected to be 0.3 microns;
[0091] The filtered nano-silica solid was placed in a drying oven for drying, the drying temperature was set at 100°C, and the drying time was 8 hours;
[0092] The dried nano-silicon dioxide solid was ground for 3 hours to disperse the agglomerated nano-silicon dioxide particles into individual nano-particles;
[0093] The ground nano-silicon dioxide powder is sieved through a sieving device to obtain a nano-silicon dioxide product with uniform particle size.
[0094] Example 2.
[0095] A new energy vehicle battery glue with fire extinguishing function, comprising the following raw materials in parts by weight:
[0096] 24 parts of organic silicone rubber, 17 parts of polyurethane, 8 parts of epoxy resin, 4 parts of nano aluminum hydroxide, 6 parts of nano magnesium hydroxide, 4 parts of zinc borate, 4 parts of phosphonate, and 4 parts of nano silicon dioxide.
[0097] The specific preparation process of new energy vehicle battery glue with fire extinguishing function is:
[0098] Add silicone rubber, polyurethane and epoxy resin into the reactor, turn on the stirring device, set the stirring speed to 150 rpm, and ensure that they are fully mixed;
[0099] Add zinc borate and phosphonate in batches, and increase the stirring speed to 400 rpm to ensure that zinc borate and phosphonate are evenly dispersed in the material.
[0100] Use a high-speed disperser to slowly add nano aluminum hydroxide, nano magnesium hydroxide, and nano silicon dioxide into the system. The speed of the high-speed disperser is set to 4000 rpm and the dispersion time is 1.5 hours to ensure that the nano materials are evenly dispersed and play a synergistic role.
[0101] Transfer the mixed sealant to the vacuum degassing equipment, turn on the vacuum pump, and perform vacuum degassing treatment; the vacuum degree is set to -0.1MPa, and the degassing time is 60 minutes to remove bubbles in the sealant and improve product quality.
[0102] The preparation method of nano aluminum hydroxide of the present embodiment is:
[0103] An aqueous solution of aluminum sulfate added with a polymer protective agent is prepared, wherein the polymer protective agent is polyethylene glycol, the amount of polyethylene glycol added is 4.5% of the mass of aluminum sulfate, and the concentration of the aluminum sulfate solution is 1.5 mol / L;
[0104] The aluminum sulfate aqueous solution was placed in a homogenizing emulsification reactor, heated to 45° C., and stirred at 1600 rpm for 30 minutes;
[0105] Slowly drip a sodium hydroxide solution with a concentration of 0.8 mol / L into the reactor, and stir continuously, control the speed to 5000 rpm, and control the reaction temperature to 35°C to obtain an aluminum hydroxide suspension;
[0106] The obtained aluminum hydroxide suspension was cooled, aged, and filtered, and the obtained filter cake was washed with deionized water; in this process, the aging treatment temperature was 20° C. and the time was 12 hours;
[0107] The azeotropic solution of n-butanol solution is added to the filter cake obtained above, and the mixture is stirred and slurried, and then azeotropic distillation is performed until the water is completely removed, and then the distillation is continued to evaporate the azeotropic solvent n-butanol, and then the obtained colloid is dried to finally obtain nano aluminum hydroxide particles; wherein, 0.6 ml of the azeotropic solvent n-butanol is added to each gram of sodium hydroxide colloid filter cake, and the drying temperature of the obtained colloid is 115° C., and the drying time is 9 hours.
[0108] The preparation method of nano magnesium hydroxide of the present embodiment is:
[0109] Homogenization: fully homogenize the desulfurization wastewater to completely precipitate the insoluble matter to obtain the primary supernatant, take samples to test the water quality of the primary supernatant, and detect the concentration of each ion;
[0110] Pretreatment: The primary supernatant is pretreated to remove reducing ions, oil, COD and heavy metal ions to obtain a suspension, which is then separated and precipitated to obtain a secondary supernatant;
[0111] Separating calcium ions: adding an excess amount of sodium carbonate solution to the secondary supernatant, the amount of sodium carbonate solution added being based on a molar ratio of carbonate ions to calcium ions of 1.2; adjusting the pH value to 7.8 with a 15wt% sodium hydroxide solution to generate a calcium carbonate precipitate, the reaction time being 30 minutes, the reaction temperature being 33°C, and separating the calcium carbonate precipitate from the supernatant to obtain a tertiary supernatant;
[0112] Preparation of magnesium hydroxide product: adding PEG-800 and excess ammonia water to the third-level supernatant, the PEG-800 addition amount is 2ml / 100ml, and magnesium hydroxide precipitate is obtained after the reaction is complete, and the magnesium hydroxide precipitate and the fourth-level supernatant are separated after sufficient aging; filtering the magnesium hydroxide precipitate, drying and dehydrating to obtain the magnesium hydroxide product, and grinding the magnesium hydroxide product with a nano grinder to obtain nano-scale magnesium hydroxide powder; wherein the ammonia water concentration is 25%, and the ammonia water addition amount is in accordance with the ratio of ammonia water to magnesium ion molar ratio of 2.2; urea is solid, and the addition amount is in accordance with the ratio of urea molar ratio to magnesium ion molar ratio of 1.1; the reaction temperature is 110°C, the reaction time is 5h, the pressure in the reactor is 2atm, and the pH is controlled to be 10; aging is performed for 1.5h after the reaction, and the aging temperature is 75°C.
[0113] The preparation method of the nano silicon dioxide of the present embodiment is:
[0114] A certain amount of tetraethyl orthosilicate was slowly added dropwise to a reactor containing deionized water, and the volume ratio of tetraethyl orthosilicate to deionized water was controlled between 1:8; at the same time, a stirring device was turned on, and the stirring speed was set at 400 rpm to ensure that the tetraethyl orthosilicate and water were fully mixed; the temperature in the reactor was maintained at 25°C; stirring was continued and the temperature was kept stable for 1.5 hours to ensure that the hydrolysis reaction was fully carried out;
[0115] Slowly add ammonia water to the solution after the hydrolysis reaction, and the speed of ammonia water addition should be controlled at 8 drops per minute to avoid uneven reaction due to excessive local ammonia water concentration; the amount of ammonia water added is determined according to the amount of tetraethyl orthosilicate, and the molar ratio of ammonia water to tetraethyl orthosilicate is 4:1; the stirring speed is maintained at 400 rpm, and the reaction temperature is still controlled at 25°C; stirring should be continued for 2.5 hours during the reaction to allow the nano-silicon dioxide particles to fully grow and stabilize;
[0116] After the reaction is completed, the obtained nano-silicon dioxide suspension is centrifuged and washed 4 times; each time, an appropriate amount of deionized water is added, and the mixture is stirred evenly and then centrifuged. The centrifugal speed is set at 4000 rpm and the centrifugal time is 12 minutes;
[0117] The washed nano-silicon dioxide suspension is filtered through a microporous filter membrane, and the pore size of the filter membrane is selected to be 0.3 microns;
[0118] The filtered nano-silica solid was placed in a drying oven for drying, the drying temperature was set at 100°C, and the drying time was 8 hours;
[0119] The dried nano-silicon dioxide solid was ground for 3 hours to disperse the agglomerated nano-silicon dioxide particles into individual nano-particles;
[0120] The ground nano-silicon dioxide powder is sieved through a sieving device to obtain a nano-silicon dioxide product with uniform particle size.
[0121] Example 3.
[0122] A new energy vehicle battery glue with fire extinguishing function, comprising the following raw materials in parts by weight:
[0123] 30 parts of organic silicon rubber, 23 parts of polyurethane, 12 parts of epoxy resin, 8 parts of nano aluminum hydroxide, 10 parts of nano magnesium hydroxide, 6 parts of zinc borate, 6 parts of phosphonate, and 8 parts of nano silicon dioxide.
[0124] The specific preparation process of new energy vehicle battery glue with fire extinguishing function is:
[0125] Add silicone rubber, polyurethane and epoxy resin into the reactor, turn on the stirring device, set the stirring speed to 150 rpm, and ensure that they are fully mixed;
[0126] Add zinc borate and phosphonate in batches, and increase the stirring speed to 400 rpm to ensure that zinc borate and phosphonate are evenly dispersed in the material.
[0127] Use a high-speed disperser to slowly add nano aluminum hydroxide, nano magnesium hydroxide, and nano silicon dioxide into the system. The speed of the high-speed disperser is set to 4000 rpm and the dispersion time is 1.5 hours to ensure that the nano materials are evenly dispersed and play a synergistic role.
[0128] Transfer the mixed sealant to the vacuum degassing equipment, turn on the vacuum pump, and perform vacuum degassing treatment; the vacuum degree is set to -0.1MPa, and the degassing time is 60 minutes to remove bubbles in the sealant and improve product quality.
[0129] The preparation method of nano aluminum hydroxide of the present embodiment is:
[0130] An aqueous solution of aluminum sulfate added with a polymer protective agent is prepared, wherein the polymer protective agent is polyethylene glycol, the amount of polyethylene glycol added is 4.5% of the mass of aluminum sulfate, and the concentration of the aluminum sulfate solution is 1.5 mol / L;
[0131] The aluminum sulfate aqueous solution was placed in a homogenizing emulsification reactor, heated to 45° C., and stirred at 1600 rpm for 30 minutes;
[0132] Slowly drip a sodium hydroxide solution with a concentration of 0.8 mol / L into the reactor, and stir continuously, control the speed to 5000 rpm, and control the reaction temperature to 35°C to obtain an aluminum hydroxide suspension;
[0133] The obtained aluminum hydroxide suspension was cooled, aged, and filtered, and the obtained filter cake was washed with deionized water; in this process, the aging treatment temperature was 20° C. and the time was 12 hours;
[0134] The azeotropic solution of n-butanol solution is added to the filter cake obtained above, and the mixture is stirred and slurried, and then azeotropic distillation is performed until the water is completely removed, and then the distillation is continued to evaporate the azeotropic solvent n-butanol, and then the obtained colloid is dried to finally obtain nano aluminum hydroxide particles; wherein, 0.6 ml of the azeotropic solvent n-butanol is added to each gram of sodium hydroxide colloid filter cake, and the drying temperature of the obtained colloid is 115° C., and the drying time is 9 hours.
[0135] The preparation method of nano magnesium hydroxide of the present embodiment is:
[0136] Homogenization: fully homogenize the desulfurization wastewater to completely precipitate the insoluble matter to obtain the primary supernatant, take samples to test the water quality of the primary supernatant, and detect the concentration of each ion;
[0137] Pretreatment: The primary supernatant is pretreated to remove reducing ions, oil, COD and heavy metal ions to obtain a suspension, which is then separated and precipitated to obtain a secondary supernatant;
[0138] Separating calcium ions: adding an excess amount of sodium carbonate solution to the secondary supernatant, the amount of sodium carbonate solution added being based on a molar ratio of carbonate ions to calcium ions of 1.2; adjusting the pH value to 7.8 with a 15wt% sodium hydroxide solution to generate a calcium carbonate precipitate, the reaction time being 30 minutes, the reaction temperature being 33°C, and separating the calcium carbonate precipitate from the supernatant to obtain a tertiary supernatant;
[0139] Preparation of magnesium hydroxide product: adding PEG-800 and excess ammonia water to the third-level supernatant, the PEG-800 addition amount is 2ml / 100ml, and magnesium hydroxide precipitate is obtained after the reaction is complete, and the magnesium hydroxide precipitate and the fourth-level supernatant are separated after sufficient aging; filtering the magnesium hydroxide precipitate, drying and dehydrating to obtain the magnesium hydroxide product, and grinding the magnesium hydroxide product with a nano grinder to obtain nano-scale magnesium hydroxide powder; wherein the ammonia water concentration is 25%, and the ammonia water addition amount is in accordance with the ratio of ammonia water to magnesium ion molar ratio of 2.2; urea is solid, and the addition amount is in accordance with the ratio of urea molar ratio to magnesium ion molar ratio of 1.1; the reaction temperature is 110°C, the reaction time is 5h, the pressure in the reactor is 2atm, and the pH is controlled to be 10; aging is performed for 1.5h after the reaction, and the aging temperature is 75°C.
[0140] The preparation method of the nano silicon dioxide of the present embodiment is:
[0141] A certain amount of tetraethyl orthosilicate was slowly added dropwise to a reactor containing deionized water, and the volume ratio of tetraethyl orthosilicate to deionized water was controlled between 1:8; at the same time, a stirring device was turned on, and the stirring speed was set at 400 rpm to ensure that the tetraethyl orthosilicate and water were fully mixed; the temperature in the reactor was maintained at 25°C; stirring was continued and the temperature was kept stable for 1.5 hours to ensure that the hydrolysis reaction was fully carried out;
[0142] Slowly add ammonia water to the solution after the hydrolysis reaction, and the speed of ammonia water addition should be controlled at 8 drops per minute to avoid uneven reaction due to excessive local ammonia water concentration; the amount of ammonia water added is determined according to the amount of tetraethyl orthosilicate, and the molar ratio of ammonia water to tetraethyl orthosilicate is 4:1; the stirring speed is maintained at 400 rpm, and the reaction temperature is still controlled at 25°C; stirring should be continued for 2.5 hours during the reaction to allow the nano-silicon dioxide particles to fully grow and stabilize;
[0143] After the reaction is completed, the obtained nano-silicon dioxide suspension is centrifuged and washed 4 times; each time, an appropriate amount of deionized water is added, and the mixture is stirred evenly and then centrifuged. The centrifugal speed is set at 4000 rpm and the centrifugal time is 12 minutes;
[0144] The washed nano-silicon dioxide suspension is filtered through a microporous filter membrane, and the pore size of the filter membrane is selected to be 0.3 microns;
[0145] The filtered nano-silica solid was placed in a drying oven for drying, the drying temperature was set at 100°C, and the drying time was 8 hours;
[0146] The dried nano-silicon dioxide solid was ground for 3 hours to disperse the agglomerated nano-silicon dioxide particles into individual nano-particles;
[0147] The ground nano-silicon dioxide powder is sieved through a sieving device to obtain a nano-silicon dioxide product with uniform particle size.
[0148] Comparative Example 1.
[0149] The difference from Example 1 is that no polyurethane was added.
[0150] Comparative Example 2.
[0151] The difference from Example 1 is that no epoxy resin is added.
[0152] Comparative Example 3.
[0153] The difference from Example 1 is that no nano aluminum hydroxide is added.
[0154] Comparative Example 4.
[0155] The difference from Example 1 is that no nano magnesium hydroxide is added.
[0156] Comparative Example 5.
[0157] The difference from Example 1 is that zinc borate is not added.
[0158] Comparative Example 6.
[0159] The difference from Example 1 is that no phosphonate was added.
[0160] Comparative Example 7.
[0161] The difference from Example 1 is that no nano silicon dioxide is added.
[0162] The sealant products prepared in Examples 1 to 3 and Comparative Examples 1 to 7 were subjected to the following performance tests:
[0163] Smoke suppression performance: Smoke density is tested in accordance with GB / T 8323.2, using flameless combustion mode, with a test radiation intensity of 25kW / m and a test time of 20min;
[0164] Vertical burning grade: tested in accordance with GB / T 2408.
[0165] The test results are as follows
[0166] Smoke density (Dm) Vertical burning level Example 1 3.2 V-0 Example 2 3.8 V-0 Example 3 3.4 V-0 Comparative Example 1 5.1 V-0 Comparative Example 2 6.7 V-0 Comparative Example 3 22.1 V-1 Comparative Example 4 18.5 V-0 Comparative Example 5 10.7 V-0 Comparative Example 6 12.9 V-0 Comparative Example 7 25.5 V-1
[0167] The new energy vehicle battery glue with fire extinguishing function provided by the present application can improve the flame retardant performance of the battery glue due to the unique physical and chemical properties of nanomaterials. Nano silicon dioxide can enhance the strength and hardness of the battery glue, and at the same time improve its flame retardant performance. The flame retardant effect of nano magnesium hydroxide and nano aluminum hydroxide is also very good, and a good flame retardant effect can be achieved at a lower addition amount.
[0168] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0169] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A new energy vehicle battery glue with fire extinguishing function, characterized in that: It includes the following raw materials in parts by weight: 24-30 parts of organic silicone rubber, 17-23 parts of polyurethane, 8-12 parts of epoxy resin, 4-8 parts of nano aluminum hydroxide, 6-10 parts of nano magnesium hydroxide, 4-6 parts of zinc borate, 4-6 parts of phosphonate, and 4-8 parts of nano silicon dioxide.
2. The new energy vehicle battery glue with fire extinguishing function according to claim 1 is characterized in that: The new energy vehicle battery glue with fire extinguishing function comprises the following raw materials in parts by weight: 27 parts of organic silicon rubber, 20 parts of polyurethane, 10 parts of epoxy resin, 6 parts of nano aluminum hydroxide, 8 parts of nano magnesium hydroxide, 5 parts of zinc borate, 5 parts of phosphonate, and 6 parts of nano silicon dioxide.
3. The new energy vehicle battery gel with fire extinguishing function according to claim 1 is characterized in that: The preparation method of the nano aluminum hydroxide is: An aluminum sulfate aqueous solution is prepared with a polymer protective agent added thereto, wherein the polymer protective agent is polyethylene glycol, the amount of polyethylene glycol added is 4%-5% of the mass of the aluminum sulfate, and the concentration of the aluminum sulfate solution is 1-2 mol / L; The aluminum sulfate aqueous solution was placed in a homogenizing emulsification reactor, heated to 45° C., and stirred at 1600 rpm for 30 minutes; Slowly drip a sodium hydroxide solution with a concentration of 0.5-1.0 mol / L into the reactor, and stir continuously, control the rotation speed to 3000-7000 rpm, and control the reaction temperature to 25-45°C to obtain an aluminum hydroxide suspension; The obtained aluminum hydroxide suspension was cooled, aged, and filtered, and the obtained filter cake was washed with deionized water; in this process, the aging treatment temperature was 20° C. and the time was 12 hours; The azeotropic solution n-butanol solution is added to the filter cake obtained above, and the mixture is stirred and slurried, and then azeotropic distillation is performed until the water is completely removed, and then the distillation is continued to evaporate the azeotropic solvent n-butanol, and then the obtained colloid is dried to finally obtain nano aluminum hydroxide particles; wherein, 0.5-0.7 ml of the azeotropic solvent n-butanol is added to each gram of sodium hydroxide colloid filter cake, and the drying temperature of the obtained colloid is 100-130°C, and the drying time is 6-12 hours.
4. The new energy vehicle battery glue with fire extinguishing function according to claim 1 is characterized in that: The preparation method of the nano magnesium hydroxide is: Homogenization: fully homogenize the desulfurization wastewater to completely precipitate the insoluble matter to obtain the primary supernatant, take samples to test the water quality of the primary supernatant, and detect the concentration of each ion; Pretreatment: The primary supernatant is pretreated to remove reducing ions, oil, COD and heavy metal ions to obtain a suspension, which is then separated and precipitated to obtain a secondary supernatant; Separating calcium ions: adding an excess amount of sodium carbonate solution to the secondary supernatant, wherein the amount of sodium carbonate solution added is in accordance with a molar ratio of carbonate ions to calcium ions of 1.1-1.3; adjusting the pH value to 7.0-8.5 with a sodium hydroxide solution having a concentration of 15 wt % to generate a calcium carbonate precipitate, the reaction time is 30 min, the reaction temperature is 30-35° C., separating the calcium carbonate precipitate from the supernatant, and obtaining a tertiary supernatant; Preparation of magnesium hydroxide product: adding dispersant and excess ammonia water to the tertiary supernatant, obtaining magnesium hydroxide precipitate after complete reaction, separating the magnesium hydroxide precipitate and the quaternary supernatant after sufficient aging; filtering the magnesium hydroxide precipitate, drying and dehydrating to obtain the magnesium hydroxide product, grinding the magnesium hydroxide product with a nano grinder to obtain nano-scale magnesium hydroxide powder; wherein the concentration of ammonia water is 25%, and the amount of ammonia water added is in accordance with the ratio of ammonia water to magnesium ion molar ratio of 2.2; urea is solid, and the amount of urea added is in accordance with the ratio of urea molar ratio to magnesium ion molar ratio of 1.1; the reaction temperature is 110°C, the reaction time is 5h, the pressure in the reactor is 2atm, and the pH is controlled to be 10; aging is performed for 1.5h after the reaction, and the aging temperature is 70-80°C.
5. The new energy vehicle battery glue with fire extinguishing function according to claim 4 is characterized in that: The dispersant is PEG-800, and the dosage is 2 ml / 100 ml, that is, 2 ml of the dispersant is added to every 100 ml of the tertiary supernatant.
6. The new energy vehicle battery glue with fire extinguishing function according to claim 4 is characterized in that: The amount of sodium carbonate solution added is based on a molar ratio of carbonate ions to calcium ions of 1.
2.
7. The new energy vehicle battery gel with fire extinguishing function according to claim 1 is characterized in that: The preparation method of the nano silicon dioxide is: Slowly drop a certain amount of ethyl orthosilicate into a reactor containing deionized water, wherein the volume ratio of ethyl orthosilicate to deionized water is controlled between 1:5 and 1:10; at the same time, turn on the stirring device, and set the stirring speed at 300-500 rpm to ensure that ethyl orthosilicate and water are fully mixed; the temperature in the reactor is maintained at 20-30°C; continue stirring and keep the temperature stable for 1-2 hours to ensure that the hydrolysis reaction is fully carried out; Slowly drip ammonia water into the solution after the hydrolysis reaction, and the dripping speed of ammonia water should be controlled at 5-10 drops per minute to avoid uneven reaction due to excessive local ammonia concentration; the amount of ammonia water added is determined according to the amount of tetraethyl orthosilicate, and the molar ratio of ammonia water to tetraethyl orthosilicate is between 3:1 and 5:1; the stirring speed is maintained at 300-500 rpm, and the reaction temperature is still controlled at 20-30°C; stirring should be continued for 2-3 hours during the reaction to allow the nano-silicon dioxide particles to fully grow and stabilize; After the reaction is completed, the obtained nano-silicon dioxide suspension is centrifuged and washed 4 times; an appropriate amount of deionized water is added each time, and the mixture is stirred evenly and then centrifuged. The centrifugal speed is set at 3000-5000 rpm and the centrifugal time is 10-15 minutes; The washed nano-silicon dioxide suspension is filtered through a microporous filter membrane, and the pore size of the filter membrane is selected to be 0.2-0.45 microns; The filtered nano-silicon dioxide solid is placed in a drying oven for drying, the drying temperature is set at 80-120°C, and the drying time is 6-12 hours; The dried nano-silicon dioxide solid is ground for 2-4 hours to disperse the agglomerated nano-silicon dioxide particles into individual nano-particles; The ground nano-silicon dioxide powder is sieved through a sieving device to obtain a nano-silicon dioxide product with uniform particle size.
8. The new energy vehicle battery gel with fire extinguishing function according to claim 7 is characterized in that: The volume ratio of ethyl orthosilicate to deionized water is 1:
8.
9. The new energy vehicle battery gel with fire extinguishing function according to claim 7, characterized in that: The molar ratio of ammonia water to tetraethyl orthosilicate is 3:1.